Research in the fields of energy and the environment (Aristotle University Thessaloniki, 2005)
The Laboratory of Heat Transfer and Environment Engineering belongs to the Mechanical Engineering Department of the Aristotle University Thessaloniki. Founded in 1990, the laboratory has along record of research and consulting activities. Most of these activities provide its modeling experience, and in particular micro-scale modeling tools, for accident simulation and the generation of machine learning training examples.